Efecto de la distancia de siembra sobre la producción de biomasa foliar de la moringa moringa oleífera lam - Segarra Lluisupa, Patricia Alexandra (2018)
The purpose of the research work about the Moringa oleifera Lam plant is to quantify the biomass production in foliage of fresh and dry material of said species, with the objective of estimating the production levels of protein provided in said material. This work was carried out in the lands of the Technical University of Machala, Academic Unit of Agricultural Sciences; performing a type of planting by seed and using a Design of Blocks Completely Random (DBCA) using the Statgraphics Centurion program to perform the analysis of variance at 95% reliability using the Fisher test. Seeding was done by seeds, which consisted of pre-germinating for 24 hours, this process consisted of placing the seeds in water and at twelve o'clock the water was changed to obtain an oxygenation process. After this step the seeds were placed in a plastic and at the same time covered with the same so that it can conserve moisture. After 5 to 8 days it began to germinate, the delay of its germination was due to the fact that in those days there was rain and therefore they needed heat so that the seed could germinate. Once the pre-germination of the seed was obtained, the field was sown directly in 12 experimental areas, which consisted of three treatments and four repetitions in different planting distances; the distances consisted of (0.5 x 0.5 m, 1.0 x 0.5 m and 1.0 x 1.0 m). To obtain the material to be processed, a 10-plant cutting sample was taken 42 days after its training cut; separating each part of the plant in: stem, leaves and rachis for their respective weighings. After the fresh weighing, the samples were dried in the environment for 4 to 5 days and then placed in the oven at a temperature of 70 ° C for 24 hours, obtaining the results of the Dry Material values ​​of each part of the sample. plant. Of the plants that were taken completely at random and at different planting distances (0.5 x 0.5, 1.0 x 0.5 and 1.0 x 1.0); in the field it was observed that in the treatment of the planting distance of 1.0 x 1.0 m and of all the replicates a higher yield was obtained in the production of biomass, since the area was higher and the higher was the incorporation of nutrients absorbed by the plant; this caused a better foliage and sprout yield to be manifested, because the plant acquires, uses and conserves its resources obtaining a correlation in its production and in its habitat to be able to sustain itself in the period of its development, considering the amount of Plants involved in each treatment, excels in this research work the planting distance of 0.5 x 0.5 m with 40,000 plants per hectare, corresponding the best production in fresh material as for the dry material.